2023
DOI: 10.1681/asn.0000000000000065
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Self-Reported Kidney Disease in Older Adults by Sexual Orientation: Behavioral Risk Factor Surveillance System Analysis (2014–2019)

Abstract: Significance Statement Studies discusses CKD disparities by age, race and ethnicity, and socioeconomics. However, despite well-documented disparities in CKD risk factors in LGBT+ adults, limited literature addresses CKD prevalence in this population. This analysis uses Behavioral Risk Factor Surveillance System (2014–2019) data to compare self-reported kidney disease prevalence in LGBT+ older adults (older than 50 years) with their heterosexual peers. Our findings indicate that LGBT+ older adults h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…In this issue of JASN , Chandra and colleagues leveraged survey data from the 2014–2017 Behavioral Risk Factor Surveillance System (BRFSS) to compare the prevalence of self-reported kidney disease among adults aged 50 years and older who identified as LGBT+ ( N =22,114) versus straight/heterosexual ( N =748,963). 2 In the study, “LGBT+” referred to individuals who identified as “lesbian,” “gay,” “bisexual,” or “something else” across all gender identities, but did not include transgender and gender-expansive individuals who identified as straight. Self-reported kidney disease was defined as a “yes” response to the question “Not including kidney stones, bladder infection, or incontinence, were you ever told you had kidney disease?”…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In this issue of JASN , Chandra and colleagues leveraged survey data from the 2014–2017 Behavioral Risk Factor Surveillance System (BRFSS) to compare the prevalence of self-reported kidney disease among adults aged 50 years and older who identified as LGBT+ ( N =22,114) versus straight/heterosexual ( N =748,963). 2 In the study, “LGBT+” referred to individuals who identified as “lesbian,” “gay,” “bisexual,” or “something else” across all gender identities, but did not include transgender and gender-expansive individuals who identified as straight. Self-reported kidney disease was defined as a “yes” response to the question “Not including kidney stones, bladder infection, or incontinence, were you ever told you had kidney disease?”…”
mentioning
confidence: 99%
“…Using a series of logistic regression models taking into account sociodemographic factors, health behaviors, access to care, and key comorbidities (HIV, heart disease, and diabetes), the authors found that older LGBT+ men were still more likely than their heterosexual peers to report kidney disease (adjust odds ratio [OR], 1.3; 95% confidence interval [CI], 1.09 to 1.54), whereas the higher self-reported kidney disease prevalence was statistically attenuated among older LGBT+ women compared with older heterosexual women (adjusted OR, 1.16; 95% CI, 0.98 to 1.37). 2…”
mentioning
confidence: 99%